2021
DOI: 10.1002/star.202100150
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Based Smart Polymeric Hydrogels and Their Prospective Applications in Biomedicine

Abstract: With increasing scientific research, knowledge, and socioeconomic awareness, research, and industrial communities are now much more interested in biopolymers‐based composite materials with multifaceted functionalities. Biopolymers are easily obtainable, economical, non‐hazardous, and abundant. Several natural and synthetic polymers have been used to prepare hydrogels, microbeads, and microfibers for controlled drug release. Due to marvelous properties, chitosan has been widely explored for medical and pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 195 publications
0
14
0
Order By: Relevance
“…31 Some natural polysaccharides are shown in Figure 4 which are commonly employed for hydrogel preparation. 32 The polysaccharides alone are unable to produce cross-linked hydrogel with higher stabilities which is the prime requisite for soil conditioners and fertilizers release applications.…”
Section: Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Some natural polysaccharides are shown in Figure 4 which are commonly employed for hydrogel preparation. 32 The polysaccharides alone are unable to produce cross-linked hydrogel with higher stabilities which is the prime requisite for soil conditioners and fertilizers release applications.…”
Section: Biopolymersmentioning
confidence: 99%
“…It is also reported that bean treatment along with chitosan inhibited necrosis caused by mosaic virus 31 . Some natural polysaccharides are shown in Figure 4 which are commonly employed for hydrogel preparation 32 …”
Section: Introductionmentioning
confidence: 95%
“…Recently, due to their specific responsiveness, plentiful progress has been made in smart hydrogels to control drug release. 152…”
Section: Key Parameters and Mechanisms For Drug Delivery Hydrogelsmentioning
confidence: 99%
“…Recently, due to their specific responsiveness, plentiful progress has been made in smart hydrogels to control drug release. 152 4.3.1 pH. pH-responsive hydrogels consist of polymerization main chains and ion side groups, which expand or contract by absorbing or releasing H + to respond to changes in environmental pH.…”
Section: Stimulus Response Of Smart Dds Hydrogelsmentioning
confidence: 99%
“…Chitosan, a natural biopolymer, also acts as a linking agent between the MSNs and biotin by forming a bioconjugate. 13,14 In the field of chemotherapeutic metallodrugs, researchers seek alternatives to platinum-based chemotherapy to reduce side effects, prevent drug resistance, and for economic viability. Ruthenium complexes have gained attention as anticancer agents due to their lower toxicity and ability to mimic iron's binding ability to biomolecules.…”
Section: ■ Introductionmentioning
confidence: 99%